An experimental study of gender and cultural differences in hue preference - Al-Rasheed, Abdulrahman S. (Frontiers in Psychology, 2015)
This paper investigates the influence of both gender and culture on colour preference. Inspection of previous studies of colour preference reveals that many of these studies have poor control over the colours that are shown – the chromatic co-ordinates of colours are either not noted or the illuminant that colours are shown under is not controlled. This means that conclusions about colour preference are made using subjective terms for hue with little knowledge about the precise colours that were shown. However, recently, a new quantitative approach to investigating colour preference has been proposed, where there is no need to summarise colour preference using subjective terms for hue (Ling et al., 2007; Hurlbert & Ling, 2007). This approach aims to quantitatively summarise hue preference in terms of weights on the two channels or ‘cardinal axes’ underlying colour vision. Here I further extend Hurlbert and Ling’s (2007) approach to investigating colour preference, by replicating their study but with Arabic and English participants, and to answer several questions: First, are there cultural differences in the shape of the overall preference curve for English and Arabic participants? Second, are there gender differences in the shape of the overall preference curve for English and Arabic participants?. Thirty eight British and 71 Saudi Arabian (Arabic) participants were compared. Results revealed that Arabic and English preference curves were found to differ, yet there was greater similarity for Arabic and English males than Arabic and English females. There was also a sex difference that was present for both Arabic and English participants. The male curve is fairly similar for both samples: peak-preference is in the blue-green region, and a preference minimum is in the red-pink/purple region. For Arabic females the preference peak appears to be in the red-pink region, whilst for English females it is shifted towards purple/blue-green.